PENERAPAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X MIPA 2 SMA NEGERI 6 SURAKARTA TAHUN PELAJARAN 2014/2015 - Ana Hariani Salim; Slamet Santosa; Umi Fatmawati (BIO-PEDAGOGI, 2015)
This study was aimed to improve critical thinking ability of the student in X MIPA 2 class of SMA Negeri 6 Surakarta in learning biology through the implementation of Problem Based Learning (PBL).This research was a Classroom Action Research which consists of three cycles. Each cycle consists of four stages: planning, action, observation, and reflection. The subject of this research were the students in X MIPA 2 of SMA Negeri 6 Surakarta academic year 2014/2015. The data were collected using critical thinking test, observation sheet, interview, and documentation. The data were validated using triangulation method. The data of test, observation, interview, and documentation were analyzed using qualitative analysis which was done in three components, they were: data reduction, data presentation, and drawing the conclusion or verification. The research procedure was using spiral method. The results show that students critical thinking ability was increased in Pre-cycle, Cycle I, Cycle II and Cycle III. The average of students critical thinking ability increase from 35,22% to 64,92%. Aspect of interpretation rise from 41,13% to 68,55%. Aspect of analysis rise from 28,23% to 58,06%. Aspect of inference increase from 38,71% to 67,74%.Aspect of evaluation increase from 43,55% to 66,94%. Aspect of explanation rise from 27,42% to 62,10%. Aspect of self-regulation rise from 32,26% to 66,13%.  This research’s conclusion was the implementation of Problem Based Learning can improve critical thinking ability of the student in X MIPA 2 class at SMA Negeri 6 Surakarta academic year 2014/2015. Keywords : Problem Based Learning, Critical Thinking